The role and histological classification of needle core biopsy in comparison with fine needle aspiration cytology in the preoperative assessment of impalpable breast lesions. Issue 2 (1st February 2001) - Ibrahim, A E K; Bateman, A C; Theaker, J M; Low, J L; Addis, B; Tidbury, P; Rubin, C; Briley, M; Royle, G T
Abstract : Aims —To investigate the role of needle core biopsy (NCB) in the preoperative assessment of impalpable breast lesions, mainly derived from the NHS Breast Screening Programme (NHSBSP) and to assess our own modifications to a suggested system for the classification of breast NCBs. Methods —The NCB, fine needle aspiration cytology (FNAC), and radiology scores from 298 women with non-palpable breast lesions presenting between January 1997 and December 1998, together with the open biopsy results (where available) were collated and analysed. Results —The mean follow up period was 15.8 months (range, 5–28). The 298 NCB specimens were categorised as follows: unsatisfactory/non-representative (B1; n = 61; 20.5%), benign but uncertain whether representative (B2r; n = 52; 17.4%), benign (B2; n = 103; 34.6%), lesions possibly associated with malignancy but essentially benign (B3a; n = 9; 3.0%), atypical epithelial proliferations (B3b; n = 10; 3.4%), suspicious of malignancy (B4; n = 7; 2.3%), and malignant (B5; n = 56; 18.7%). Excision biopsy was performed in 43 cases within the B1 (n = 19), B2r (n = 8), B2 (n = 8), and the B3a (n = 8; data unavailable in one case) categories, revealing malignancy in 18 (42.8%) cases and in 65 cases within the B3b, B4, and B5 categories, revealing malignancy in 64 cases (98.5%). The sensitivity of NCB for malignancy was 87.7%, with a specificity and positive predictive value of 99.3% and 98.5%, respectively. FNAC had an inadequacy rate of 58.7%, a complete sensitivity of 34.5% and a specificity of 47.6%. Conclusions —This study confirms the value of NCB in the preoperative assessment of impalpable breast lesions. Two new categories are suggested for the NCB classification; category B2r for benign breast tissue where representativeness is uncertain, and the subdivision of category B3 into B3a for benign lesions potentially associated with malignancy (for example, radial scars and intraduct papillomas) and B3b for more worrisome atypical epithelial proliferations. These will aid the accurate audit of NCB and identify more clearly the intellectual pathway leading to a particular assessment.